Sugarcane/soybean intercropping with reduced nitrogen addition promotes photosynthesized carbon sequestration in the soil - Zhang, Tantan; Tang, Hu; Peng, Peng; Ge, Shiqiang; Liu, Yali; Feng, Yuanjiao; Wang, Jianwu (Frontiers in Plant Science, 2023)
Sugarcane/soybean intercropping with reduced nitrogen (N) addition has improved soil fertility and sustainable agricultural development in China. However, the effects of intercropping pattern and N fertilizer addition on the allocation of photosynthesized carbon (C) in plant-soil system were far less understood. In this study, we performed an 13 CO 2 pulse labeling experiment to trace C footprints in plantsoil system under different cropping patterns (sugarcane monoculture (MS), sugarcane/soybean intercropping (SB)) and N addition levels (reduced N addition (N1) and conventional N addition (N2)).Our results showed that compared to sugarcane monoculture, sugarcane/soybean intercropping with N reduced addition increased sugarcane biomass and root/shoot ratio, which in turn led to 23.48% increase in total root biomass. The higher root biomass facilitated the flow of shoot fixed 13 C to the soil in the form of rhizodeposits. More than 40% of the retained 13 C in the soil was incorporated into the labile C pool (microbial biomass C (MBC) and dissolved organic C (DOC)) on day 1 after labeling. On day 27 after labeling, sugarcane/soybean intercropping with N reduced addition showed the highest 13 C content in the MBC as well as in the soil, 1.89 and 1.14 times higher than the sugarcane monoculture, respectively. Moreover, intercropping pattern increased the content of labile C and labile N (alkaline N, ammonium N and nitrate N) in the soil. The structural equation model indicated that the cropping pattern regulated 13 C sequestration in the soil mainly by driving changes in labile C, labile N content and root biomass in the soil. Our findings demonstrate that sugarcane/soybean intercropping with reduced N addition increases photosynthesized C sequestration in the soil, enhances the C sink capacity of agroecosystems.